Effects of over-ground walking and cognitive rehabilitation on cognition, brain-derived neurotrophic factor, participation and quality of life among stroke survivors: a study protocol (2020)
Background: Cognitive rehabilitation (CR) is an important component of stroke rehabilitation. Most of the strategies used for this purpose are not readily affordable. This is the protocol of a trial to investigate the effects of over-ground walking (OGW) exercise and CR on cognitive function among stroke survivors. Methods: This is a three-centre, single blind, randomised controlled trial (RCT). Fifty-seven stroke survivors with mild to moderate cognitive impairments will be recruited from three healthcare facilities and randomly assigned into three groups. Group A will receive moderate intensity OGW exercise. Group B will receive CR using an adapted cognitive intervention comprising an attention and a memory tasks. Group C will receive combine OGW and CR exercise. All interventions will be thrice weekly for 8 weeks. Outcomes to be assessed at baseline, 4th and 8th week of interventions are cognition, brain-derived neurotrophic factor (BDNF), quality of life and participation using Mini-Mental State Examination, Melsin brand ELISA kit, stroke-specific quality of life and London Handicap Scale, respectively. Friedman and Kruskal–Wallis tests will be used for within-group and between-group comparison of data. Discussion: This trial is the first to examine the effect of OGW exercise on cognition and BDNF among stroke survivors.